2009
DOI: 10.1124/dmd.108.026286
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Human Corneal Epithelial Cell Model As a Surrogate for Corneal Permeability Assessment: Metabolism and Transport

Abstract: ABSTRACT:The recently introduced Clonetics human corneal epithelium (cHCE) cell line is considered a promising in vitro permeability model, replacing excised animal cornea to predict corneal permeability of topically administered compounds. The purpose of this study was to further characterize cHCE as a corneal permeability model from both drug metabolism and transport aspects. First, good correlation was found in the permeability values (P app ) obtained from cHCE and rabbit corneas for various ophthalmic dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 25 publications
5
73
0
Order By: Relevance
“…5 Hence, cationic drugs may utilize some uptake transporters for their permeation across biological membranes. 19,20,28 Presence of transporters like OCT in the conjunctival and corneal epithelial cells to reabsorb various endogenous amines in the tear fluid has been well recognized. [6][7][8] Moreover, evidence from molecular biology studies from our laboratory and others showed the presence of various OCT in cornea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Hence, cationic drugs may utilize some uptake transporters for their permeation across biological membranes. 19,20,28 Presence of transporters like OCT in the conjunctival and corneal epithelial cells to reabsorb various endogenous amines in the tear fluid has been well recognized. [6][7][8] Moreover, evidence from molecular biology studies from our laboratory and others showed the presence of various OCT in cornea.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, transport processes due to OCT were showed using ex vivo models in excised cornea, 19 in vitro corneal cells, 19 and excised conjunctiva 20 for understanding the functional importance of OCT. However, from the literature it was also evident that cell line studies did not reveal (due to minimal expression of transporters in the cell lines) the active functional role of OCT in transporting the administered eye drop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal permeability of these prostaglandin analogs are in agreement with previously reported values in the literature. 9,21 It was noticed that both latanoprost and travoprost (ester prodrugs) rapidly hydrolyze to its free acid form thus substantiating the fact that the free acid form is responsible for IOP reduction. But in case of bimatoprost (amide prodrug), hydrolysis was partial, though the free acid form was the predominant species.…”
Section: Cellular Accumulation Of Bimatoprost In Rpcec In the Presencmentioning
confidence: 99%
“…[6][7][8] In addition, mRNA expression levels of other isoforms of MRP, MRP1 and MRP3, have been reported in the human cornea, though functional activity and localization still remain to be assessed. 9,10 With an array of effl ux transporters being identifi ed on the corneal epithelium and along with our earlier report that clearly demonstrates the role of effl ux pumps in restricting ocular bioavailability, it is imperative to screen potential ocular therapeutic agents for interaction with effl ux pumps.…”
Section: Hariharan Et Al 488mentioning
confidence: 99%